Lower income group strategies towards buying a house in Kelantan / Aizat Affendi Abdullah and Mohd Hafiz Saberi - Abdullah, Aizat Affendi; Saberi, Mohd Hafiz (2018)
Housing forms one of the basic needs of human. However, as we can see, not many people in Malaysia is afford to buy a house. Low-income communities continue to face various barriers in buying homes Lowincome group continue to face barriers to buying a home, especially because of the lack of income and net worth. The aim of this study Is to to determine the strategies of lower income group towards buying a house in Kelantan. The need of this assessment is to ensure that the findings for this research can help the low-income group to buy a house. The objectives of this paper is to determine the factors that influence the lower income groups to buy a house, to determine the difficulties to buy a house by lower income groups, and the latest one is to identify the strategies of lower income group towards buying a house. The respondents are among the businessmen, government sectors and private sectors. A study was conducted among on an overall of the lower income group that residing in area of Pasir Mas Kelantan. To achieve the objectives of this study a questionnaire survey was used to obtain the required data. A The detailed and efficient research is required to examine the steps that need to be done by the lower income groups to buy a house. The recommendations of this study will help the lower income groups to solve this problem.